The performance of the Romanian pension system from the perspective of sustainability, adequacy and equity - Mladen, Luise (Journal of Economic Development, Environment and People, 2023)
Ensuring financial security in old age is an important goal of all contemporary societies. Public pension systems have become a foundation of income security for the elderly in most countries, being one of the main pillars of the welfare state. An effective pension system is one that manages to achieve its objectives, namely combating poverty among the elderly and maintaining a decent standard of living in old age, under the conditions of ensuring intra- and intergenerational equity. In the context of an aging population, the major challenge for our societies is to ensure an adequate income for the elderly without putting excessive pressure on the younger generations. The aim of the paper is to achieve a multidimensional analysis of the performance of the pension system in Romania from the perspective of sustainability, adequacy and equity.